"Orationi al cepo overo a la scala": le laude della Confraternita bolognese di S. Maria della morte - Filocamo, Gioia <1967> (Alma Mater Studiorum - Università di Bologna, 2015)
La Confraternita bolognese di S. Maria della Morte, istituita nel 1336 sull’onda della predicazione del frate domenicano Venturino da Bergamo, è la più antica e meglio documentata compagnia italiana ‘di giustizia’. Possedeva un laudario conosciuto attraverso 12 manoscritti redatti tra XV e XVI secolo, dove le laude seguono il “confortatorio” che insegnava ai confratelli come relazionarsi col condannato e prepararlo a morire in perfetto spirito cristiano. Nelle laude l’identificazione poetica tra Cristo e il condannato era funzionale allo scopo di convertire il criminale in santo, convincendolo che la sua morte aveva una funzione redentrice per sé e la città stessa. L’assoluzione plenaria poteva essere ottenuta solo tramite una morte completamente accettata e un pentimento sincero. La dissertazione indaga le tematiche espresse dalle laude e le motivazioni forti che spingevano i confortatori a intraprendere questa peculiare attività assistenziale. === During the fifteenth century a number of laude were destined for the spiritual edification of those condemned to death. The Bolognese confraternity of S. Maria della Morte, founded in 1336 and among the oldest and best-documented Italian Companies of Justice, had a laudario known now in some twelve sources, mostly dating from the second half of the fifteenth century. These laude are often connected to the ‘consolation manuals’ (confortatori) written in some Italian confraternities in order to instruct brethren who in the few hours before death prepared the prisoner to die in a Christian spirit. In the justice laude the poetic identification between the condemned and Christ or martyrs was functional to the main aim of the brethren who assisted prisoners destined to die: by turning the criminal into a saint he could be convinced that his death had a precise function. Indeed, plenary absolution in the afterlife could be obtained through a truly accepted death. The laude in the confortatori clearly had the function of reinforcing these feelings, but there is little evidence on just how this task was realized in practice. During the night preceding the execution of the prisoners, the brethren sought to turn every criminal into a saint: in the end he must have the conviction that his death had a precise function, and thus he would attain complete inner peace and total acceptance of his sentence. This serene attitude was the basis for a plenary absolution in the afterlife, obtained through a death that was fully accepted. This dissertation focuses on the strong motivation of the brethren who decided to enter this kind of confraternity.